Effects of cultivars and dry fraction on nutritional and phytochemical compounds of faba beans (Vicia faba L.) - Xiao, Tianzhen; Witt, Marie Louise Pontoppidan; Gøkhan, Kübra Yilmaz; Lokuge, Gayani Madushani Sirinayake; Eybye, Karin Loft; Kankaanpää, Santeri; Nurmi, Markus; Kahala, Minna; Larsen, Lotte Bach; Poulsen, Nina Aagaard (Academic Press, 2025)
This study aims to examine the variation in bioactive compounds in faba bean seeds among different cultivars with consideration of differences introduced by growing conditions, including minerals, low molecular weight sugars (LMWS), raffinose family oligosaccharides (RFOs), total polyphenols content (TPC), trypsin inhibitor activity (TIA), and vicine and convicine (v-c). Besides, a faba bean protein concentrate from air classification was studied to provide insights into the nutritional modifications resulting from protein refinement. Faba beans had abundant potassium (1391.77 mg/100 g on average) and iron (5.48 mg/100 g). Sucrose was the major LMWS, and verbascose was the primary RFO in faba beans, displaying a higher variability across cultivars compared to growing conditions. The analysis of different faba bean varieties also revealed varying levels of TPC in faba bean seeds (1.29–2.37 mg gallic acid equivalents/g), v-c (1.46–10.5 mg/g; 0.21–2.37 mg/g), and TIA (18.45–39.51 U/mg). Air classification significantly enriched the content of most minerals, as well as verbascose and stachyose, but reduced the content of calcium and raffinose. This indicates that certain components were redistributed during the separation of proteins and starch granules. The study reinforces the role of faba bean varieties in determining essential nutritional attributes while demonstrating limited influence from growing conditions.
Keywords: faba bean; minerals; oligosaccharides; polyphenols; trypsin inhibitor; vicine-convicine; antinutrients; varieties